2013
DOI: 10.1007/s40069-013-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Compressive Strength of Concretes Containing Silica Fume and Styrene-Butadiene Rubber (SBR) with a Mathematical Model

Abstract: This paper deals with the interfacial effects of silica fume (SF) and styrene-butadiene rubber (SBR) on compressive strength of concrete. Analyzing the compressive strength results of 32 concrete mixes performed over two water-binder ratios (0.35, 0.45), four percentages replacement of SF (0, 5, 7.5, and 10 %) and four percentages of SBR (0, 5, 10, and 15 %) were investigated. The results of the experiments were showed that in 5 % of SBR, compressive strength rises slightly, but when the polymer/binder materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
2
18
1
1
Order By: Relevance
“…This tendency resembles Shafieyzadeh's findings. Shafieyzadeh (2013) reported that the compressive strength of concrete with polymer-binder and SF increased about 6-15.5 %, but he used 5 % of polymer-binder ratio and 5 % of SF which was greater amount than our study. Such a high compressive strength development was attributed to the marked water-reducing effect and improved bonds between cement hydrates and aggregates due to the incorporation of polymer powder (Lho et al 2010).…”
Section: Pore Size Distributioncontrasting
confidence: 71%
See 2 more Smart Citations
“…This tendency resembles Shafieyzadeh's findings. Shafieyzadeh (2013) reported that the compressive strength of concrete with polymer-binder and SF increased about 6-15.5 %, but he used 5 % of polymer-binder ratio and 5 % of SF which was greater amount than our study. Such a high compressive strength development was attributed to the marked water-reducing effect and improved bonds between cement hydrates and aggregates due to the incorporation of polymer powder (Lho et al 2010).…”
Section: Pore Size Distributioncontrasting
confidence: 71%
“…Concrete contains mineral admixtures and latexes for various reasons at present-day. These materials can increase abrasion strength or durability and decrease permeability (Shafieyzadeh 2013). Various studies have been conducted on the durability and strength of concrete with mineral admixtures and polymers (Bhikshma et al 2009;Rozenbaum et al 2005;Wang et al 2005;Bhanjaa and Sengupta 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that adding a polymeric compound to a cementitious material can improve the material properties such as strength, durability, and interfacial bond between the newly applied material and the existing substrate [1][2][3][4][5][6][7][8][9][10][11][12]. Therefore, incorporating polymers in patch repair cement mortars is common for better repair work of various reinforced concrete (RC) structures, including bridges, dams, high-rise buildings, pavements, and marine concrete structures [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of researchers have introduced a relationship between the concrete compressive strength and curing time with different logarithmic equations [23,[33][34][35]. Yeh, I.C.…”
Section: Concrete Compressive Strength Development Over Time Modelmentioning
confidence: 99%